2004
DOI: 10.3733/ca.v058n01p18
|View full text |Cite
|
Sign up to set email alerts
|

Food insecurity prominent among low-income California Latinos

Abstract: Food security is defined as access by all people at all times to enough food for an active, healthy life. In a study of 212 low-income Latino households in California, 45% were food insecure without hunger; 13% food insecure with moderate hunger; and 3% food insecure with severe hunger. Food insecurity was associated with a decline in household supplies of both nutritious and less nutritious foods. Among preschool children, the number of servings per day of all food groups was significantly correlated with hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…When one controls for household income, region of residence, and household composition, food security in Latino households has been consistently lower than national rates (82% versus 89%) (Melgar-Quinonez & Kaiser, 2004; Nord et al). In low-income California Latino households (n = 212) for example, 45% were marginal food secure, 13% low food secure, and 3% very low food secure (Kaiser et al, 2004). …”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…When one controls for household income, region of residence, and household composition, food security in Latino households has been consistently lower than national rates (82% versus 89%) (Melgar-Quinonez & Kaiser, 2004; Nord et al). In low-income California Latino households (n = 212) for example, 45% were marginal food secure, 13% low food secure, and 3% very low food secure (Kaiser et al, 2004). …”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies of food security and nutritional outcomes of preschool-aged Mexican-American children (n = 211 and 256) found that rates of overweight or obese children (37%) peaked among low and very low food secure families (Kaiser et al, 2002; Kaiser et al, 2003). In very low food secure households, children were less likely to meet U.S. Department of Agriculture (USDA) Food Guide Pyramid recommendations, and this was associated with fewer household supplies of both nutrient-dense (oranges, apples, bananas, carrots, beef, fish) and less nutritious foods (soda, cookies, chips, gelatin and powdered chocolate flavoring) (Kaiser et al, 2004; Quandt, Arcury, Early, Tapia & Davis, 2004). In greater than 90% of households reporting very low food security, traditional foods such as corn tortillas, white rice, onions, beans, and cooking oil remained stable food items, as well as nontraditional foods such as hot dogs, sweetened cereal, ice cream, candy and fruit-flavored punches (Kaiser et al, 2004).…”
Section: Literature Reviewmentioning
confidence: 99%
“…UCCE research among low-income Latino families in California found that food insecurity -de ned as the lack of access of all people at all times to enough food for an active, healthy life -is associated with lower household supplies and consumption of fruits and vegetables (Kaiser et al 2003(Kaiser et al , 2004. In addition to household nancial constraints, the limited availability of fruits and vegetables in low-income neighborhoods also appears to account for some of the disparities in intake across ethnic groups and socioeconomic levels (Morland and Filomena 2007).…”
Section: Low Consumption Nationallymentioning
confidence: 99%
“…For example, research by Vega et al (2009) andDevlin, Roberts, Okaya, andXiong (2006) reported that Latinos living in the United States (particularly barrios) were more likely to develop diabetes than Latinos living in Latin America. In CA, the issue of how poverty affects health and education has been documented to be related to low-income Latinos' (particularly in rural communities) accessibility to quality food (Kaiser et al, 2004) and quality schooling (Gándara & Contreras, 2009;Valenzuela, 1999).…”
Section: Latino Health: (In)direct Effects Of Educational Successmentioning
confidence: 98%